Dreamlike Objects. Surrealistic Kitsch in Benjamin and Buñuel - Mecacci, Andrea (Aisthesis, 2025)
Benjamin’s reflection on kitsch fits with strong traits of originality into the more overall focus on this category developing in Germany in the first thirty years of the twentieth century. This survey will be summarily divided into three steps. Initially, an analysis of the essay Traumkitsch (Dream Kitsch), an inevitable starting point; an analysis that is not textual but aimed at emphasizing certain perspective points and taking into account the observations on kitsch contained in the Passages. This part will be followed by the consideration of a possible placement of Benjamin’s kitsch within the debate of the time, and finally, the connection with Surrealism will be explored not by relating Benjamin’s theses to Breton’s canonical texts but rather to some of Buñuel’s reflections on the psychology of the inanimate, a dimension that not coincidentally serves as a critical undercurrent in Benjamin’s kitsch as well.